The Cultural Role of Traditional Leaders in Initiating The Formulation of Sharia Regional Regulations in West Sumatra - Mughits, Abdul; Syafruddin; Fathorrahman (Islam Transformatif : Journal of Islamic Studies, 2025)
Abstract This research aims to explore and analyze the role of the traditional leaders (Ninik Mamak) in West Sumatra in initiating and controlling the implementation of Sharia Regional Regulations (Perda Syariah) and how they act as a bridge between culture and religion. These traditional leaders play an important role in maintaining the balance between Minangkabau customs and the principles of Islamic law. The data sources for this qualitative research were the results of observations of Minangkabau customary life phenomena, interviews with Minangkabau customary figures and relevant parties, and documentation of research findings and news related to the Sharia Regional Regulation in West Sumatra. After analyzing the data using a sociological approach, specifically Max Weber's theories of Charisma and Authority, it was found that the traditional leaders of the Ninik Mamak played a significant role in initiating and controlling the implementation of the Sharia Regional Regulation in West Sumatra, while also taking on a moderating role between culture and religion. This is in line with the motto "Adat Basandi Syarak, Syarak Basandi Kitabullah" (ABS-SBK). Their presence has helped create harmony between Minangkabau culture and Sharia law in the region, while also preserving cultural sustainability and ensuring the implementation of Islamic legal principles in accordance with the Minangkabau people's way of life. Abstrak Penelitian ini bertujuan mengeksplorasi dan menganalisis peran Ketua Adat (Ninik Mamak) di Sumatera Barat dalam menginisiasi dan mengontrol implementasi Peraturan Daerah Syariah (Perda Syariah) dan bagaimana mereka berperan sebagai penghubung antara budaya dan agama. Para pemimpin tradisional ini memiliki peran penting dalam menjaga keseimbangan antara adat Minangkabau dan prinsip-prinsip hukum Islam. Sumber data penelitian kualitatif ini adalah hasil dari observasi terhadap fenomena kehidupan adat Minangkabau, wawancara dengan para tokoh adat Minangkabau dan para pihak terkait, dan dokumentasi hasil penelitian serta berita-berita yang terkait dengan Perda Syariah di Sumatera Barat. Setelah data tersebut dianalisis dengan pendekatan sosiologis, yakni teori Karisma dan Otoritas Max Weber menunjukkan peran signifikan para tokoah adat Ninik Mamak dalam menginisiasi dan mengnotrol implementasi Perda Syariah di Sumatera Barat, sekaligus mengambil peran moderat antara budaya dan agama. Hal itu selaras dengan semboyan Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK). Kehadiran mereka telah membantu menciptakan harmoni antara budaya Minangkabau dan hukum Syariah di wilayah tersebut sekaligus menjaga keberlanjutan budaya dan memastikan penerapan prinsip-prinsip hukum Islam yang sesuai dengan cara hidup masyarakat Minangkabau.